IMPROVING THE QUALITY OF PUBLIC SERVICE BY BUS TRANSPORT ON THE EXAMPLE OF THE CITY OF TASHKENT - Назаров А. А. (Bright Mind Publishing, 2025)
With the declaration of independence, the urban transport of the Republic faced the issue of improving urban transport, in particular bus transport in the city of Tashkent. The article considers the causes and prospects of this issue.
Keywords: Independence, transport. bus, city, quality, improvement, Toshshaarchism.